Alkaline phosphatase isoenzyme analysis in umbilical cord blood of healthy term neonates - Hemavathi, S.; Sathiyapriya, V.; Rekha, C.; Seeralar, A. T. Arasar; Dolia, Pragna B.; P., Abinaya (International Journal of Contemporary Pediatrics, 2024)
Background: Alkaline phosphatases are isoenzymes that hydrolyze the organic phosphate in the extracellular space to free phosphates; mostly they are present on the outer layer of the cell membrane similar to that on hepatocytes. The human body contains four isoenzymes: they are hepatic/bone/renal alkaline phosphatase (L/B/K ALP), intestinal alkaline phosphatase (IALP), placental alkaline phosphatase (PLALP isoenzyme), and germ cell alkaline phosphatase (GCALP). In clinical practice, alkaline phosphatase (ALP) is routinely measured as a marker of bone and hepatic function. In the field of neonatology, it is used in diagnosing and indicating the severity of metabolic bone disease (MBD) in preterm newborns. It is also used as an early predictor of neonatal jaundice. The current study is aimed at detecting the specific isoenzyme form of alkaline phosphatase elevated in the umbilical cord of newborns and its association with hyperbilirubinemia. Methods: The study included 30-term newborns in a tertiary care hospital in Velappanchavadi, Chennai. After birth, cord blood was collected for the determination of alkaline phosphatase isoenzyme in the serum. The average alkaline phosphatase activity in the cord blood serum was 109±35 IU/l. The average percentage of alkaline phosphatase activity after treatment with heat, phenylalanine, and urea were 6, 11.5, and 87% respectively. Results: It was evident that the isoenzyme form present in the umbilical cord of term healthy neonates is of intestinal origin. Conclusions: The elevated intestinal form of alkaline phosphatase indicates an immature liver and thereby predicts the future development of hyperbilirubinemia.